Effectiveness of buteyko breathing technique on level of Peak expiratory flow rate and asthma symptoms among Patients with bronchial asthma. - K.KARPAGAM; DR.P.MANGALAGOWRI; DR.S.ARUNA (International Journal of Pharma and Bio Sciences, 2017)
This study is intended to determine the effectiveness of Buteyko breathing technique on level of peak expiratory flow rate (PEFR) and asthma symptoms among patients with Bronchial asthma. A quasi- experimental design was choosen to conduct this study, the investigator selected 60 samples by using convenient sampling technique. After the sample selection informed consent obtained, the investigator assessed the PEFR level by using Peak expiratory flow meter and asthma symptoms by using asthma control questionnaire in both experimental and control group. Then the experimental group was trained on buteyko breathing exercises. Repetitive trials were given to the subjects 20-30 minutes twice a day, for duration of 3 weeks. The control group was treated with hospital routine measures. The investigator assessed PEFR Level by using PEFR flow meter and the asthma symptoms by using asthma control questionnaire in both experimental and control group, after three week of buteyko repetitive trials. There was statistically significant improvement in the PEFR level and reduction in the asthma symptoms in the experimental group after Buteyko breathing technique than the control group among patients with Bronchial asthma.(p<0.001). Hence the Buteyko breathing technique effective in treatment of Bronchial asthma.